PENGARUH KEAHLIAN PROFESIONAL, INDEPENDENSI, DAN TEKANAN ANGGARAN WAKTU TERHADAP PENDETEKSIAN KECURANGAN (Studi Empiris Pada Badan Pemeriksa Keuangan Perwakilan Provinsi Riau) - Widya Pangestika; Taufeni Taufik; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The objectives of this research are to analyze expertise of professional, independence, and time budget pressure that can affect the fraud detection. The population of this study are independent auditors who have worked for BPK RI Perwakilan Province of Riau. Meanwhile the sample of this research are 53 auditors. Types of data used are primary data by the method of data collection using questionnaire. The method of data analysis used in this study is multiple regression with the help of software SPSS version 17. The result showed that expertise of professional and independency significant effect on fraud detection. Than time budget pressure not effect to fraud detection with significance value of expertise of professional 0.001, independency 0.000, and time budget pressure 0.716. The value of Adjust R squarets aqual to 0.910, which mean 91% of independent variables in the study was able to influence the dependent variable, while the remaining 9% is explained by other variables not included in this study.Keywords : Expertise of Professional, Independence, time budget pressure, Fraud Detection